Les usages sociaux des technologies de l’information et de communication chez les étudiant·e·s internationaux et internationales en période de confinement lié à la pandémie de la COVID-19 au Québec - Jorge Frozzini; Joseph Lévy; Daniel Côté; Jessica Dubé; Farrah Bérubé; Aïcha Andjari Tounkara; Gabriel Bernard (Communiquer)
This article explores the social uses of ICTs and their impact on the quality of life of international students (IS) in the context of the 2020 Quebec lockdown in response to the COVID-19 pandemic. Semi-structured online interviews with 40 ISTs revealed that ISTs use social media for communication and peer support and use applications for multiple purposes (information, entertainment, shopping, games). Video conferencing platforms have played a significant role in enabling participation in online activities and maintaining relationships with family and friends. Finally, ICTs have made it possible to cope with confinement conditions, but they have also had repercussions on the quality of life that have been assessed as problematic (increased time spent online, addiction, anxiety, fatigue).